(untitled) (UNA MIRADA A..., 2024)
Visual training has emerged as a crucial tool in high-performance sports, where every millisecond counts. This type of training focuses on improving essential visual skills, such as spatial awareness and decision-making, which can make the difference between winning and losing. Chelsea F.C. implemented an innovative visual training program for its women’s team during the 2020-2021 season, led by specialist Edouard Lafosse. This program included exercises to enhance reaction time, coordination, and decision-making under pressure, utilizing advanced technologies like FitLights and Dynavision D2. The results were remarkable, especially among the goalkeepers, who showed significant improvements in their reaction times. Ann-Katrin Berger stood out with a record time of 260 milliseconds after just 10 sessions. The impact of the training was reflected in the team’s performance, which won the FA Women’s Super League and the FA Cup, and reached the final of the UEFA Champions League. The improvement in decision-making and reaction times was evident in their defensive performance. In summary, visual training not only enhanced individual skills but also contributed to the collective success of the team, highlighting the importance of innovation in sports.